PENGARUH GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI PEMODERASI - Mishelei Loen, SE., M.Si. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2023)
This study aims to examine the Effect of Good Corporate Governance and Corporate Social Responsibility on Company Value with Financial Performance as a Moderator, Mining Companies Registered on the IDX for the 2020-2022 period. The data used in this research is quantitative data. The sampling technique using purposive sampling obtained a total sample of 66 data. The results of the study show that GCG has no effect on firm value. Corporate Social Responsibility has an effect on company value. Financial performance cannot moderate the relationship between GCG and company value. Financial performance is able to moderate the relationship between CSR disclosure and firm value.